The effect of simultaneous application of contrast temperature therapy and intermittent compression on recovery following exercise induced muscle damage - Holroyd, Wayne (Division of Physiotherapy, 2015)
Objective: To determine the effects of the simultaneous application of contrast temperature therapy with intermittent compression as a recovery strategy for the quadriceps muscle following exercise induced muscle damage in moderately active adult males.